Propriedades físico-hídricas do solo e desenvolvimento radicular do cafeeiro - Silva, Érika Andressa da (2017)
In the region of the High São Francisco River, in Minas Gerais, Brazil, a management system uses intense soil revolving and deep preparation of the coffee-planting furrows, grass with periodic cuts in the interlines, and heaping to the line of the main culture, in addition to doses of gypsum above what is conventionally recommended in literature. The main objective is to increase the content of calcium in the depth of the soil profile. This system has been adopted by many coffee producers, gaining prominence for the promotion of coffee root development in depth as a strategy to escape the issue of drought, allowing better use of water from the subsoil. However, there are still few scientific studies regarding its implementation in the different pedological units of the region. Therefore, this study aimed at evaluating: i) the potential of the management system for promoting positive changes in the structure of Oxisol, Cambisol and Nitosol; ii) its capacity for conditioning physical-hydric aspects that favor the development of coffee root system; iii) the influence of implementation time over pore configuration and the distribution of the root system in very clayey Oxisol. We also conducted a study to compare methods for determining the stability of soil aggregates. The study is being published in four articles. The most efficient methods for obtaining the aggregation indexes derived from specific ultrasonic energy. In the second article, while studying gibbsitic oxidic Red Oxisol, we verified that the management influences aggregate stability in size 4-8 mm classes, given that the critical energy necessary for disaggregation of this class of aggregates was superior to that observed in native wood. In the third article, w hile evaluating Nitosol, Cambisol and Oxisol, after 5 years of implementing the management system, we verified that all soils underwent structural changes, but with distinct impacts. The most benefits occurred in the Cambisol, in which management, at layers of 0.20-0.40 m, caused the increase in the volume of large and thin macropores (>147; 147-73 μm), responsible for the greater aeration and quick internal drainage of the soil, as well as increase of large macropores (73-49 and 49-29 μm), responsible for the water available to the plants. In the fourth article, we verified that the coffee crops in gibbsitic Oxisol, with 3 years of age, already presented root system with conformity typical of an adult plant, reaching depth larger than 1 m. The management system is indicated for Oxisol and Cambisol of this region.